Unexpected solar-cycle variation of acoustic mode power in Sun-as-a-star observations. Issue 3 (9th June 2022) - Howe, Rachel; Chaplin, W J; Elsworth, Y P; Hale, S J; Nielsen, M B
ABSTRACT: We examine the solar-cycle variation of the power in the low-degree helioseismic modes by looking at binned power spectra from 45 yr of observations with the Birmingham Solar Oscillations Network, which provides a more robust estimate of the mode power than that obtained by peak fitting. The solar-cycle variation of acoustic mode power in the 5-min band is clearly seen. Unusually, even though Cycle 24 was substantially weaker in terms of surface magnetic activity than Cycle 23, the reduction in mode power at solar maximum is very similar for the two cycles, suggesting that the relationship between mode power and magnetic activity is more complex than has previously been thought. This is in contrast to the mode frequencies, which show a strong correlation with activity with only subtle differences in the response across different solar cycles.